Analisis Penggunaan Similes dan Metaphors pada Novel Berjudul “Hard Time” sebagai Tulisan Deskriptif - Lilik Damayanti (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
Figurative language is a way to engage readers and deliver them through writing in a more creative form. The two categories of figurative languages that are most widely known are similes and metaphors. The purpose of this study was to analyze the use of similes and metaphors contained in a literary work in the form of a novel entitled "hard times". The method used in this study is descriptive qualitative by describing the results of the analysis in the form of data which has taken from one section or chapter found in the novel by Charles Dickens, which consists of 10 pages. The results of this study are the use of similes is more emphasized on the use of "as" than the use of "like". the use of similes "as" and "like" in the novel are used as a form of figurative speech which is made as a comparison between two objects of various types. Using similes in the novel can give a better sense and convey it to the reader. Whereas for metaphors there are only found five sentences because in this writing use more direct speech or direct quotations to emphasize the function of metaphor to live the story in Novel